Prevalence and Associated Factors of Perinatal Asphyxia in Neonates Admitted to Ayder Comprehensive Specialized Hospital, Northern Ethiopia: A Cross-Sectional Study - Gebrehiwot Teklehaimanot Gebregziabher; Fikaden Berhe Hadgu; Haftom Temesgen Abebe (International Journal of Pediatrics)
Background. Perinatal asphyxia is defined as the inability of the newborn to initiate and sustain enough respiration after delivery and is characterized by a marked impairment of gas exchange. It is one of the most common causes of neonatal mortality and morbidity. There are very few studies on perinatal asphyxia in Tigray, and so this study is aimed at assessing the prevalence and associated factors of perinatal asphyxia in Ayder Comprehensive Specialized Hospital NICU, Tigray, Ethiopia. Methods. An institution-based cross-sectional study design was conducted among neonates admitted to Ayder Comprehensive Specialized Hospital from January 1, 2016, to December 30, 2017. Medical records of 267 neonates admitted to the neonatal intensive care unit were selected by a systematic sampling method, and relevant information was collected using a checklist. The data was analyzed using SPSS version 20. Descriptive statistics were computed to determine the prevalence of birth asphyxia and sociodemographic and obstetrics data. Binary logistic regression was used to test associations between the associated factors and perinatal asphyxia. First bivariate analysis was performed to assess the association without controlling the effect of other independent variables. Variables with P value < 0.25 were fitted to the multivariable binary logistic regression model. Finally, variables with P value < 0.05 were expressed as associated factors of perinatal asphyxia. Results. Of the 267 neonates, 48 neonates had perinatal asphyxia, giving a prevalence of 18%. Prolonged labor (AOR=5.19, 95% CI: 1.73-15.63, P=0.003), presence of meconium (AOR=4.17, 95% CI: 1.34-12.98, P=0.014), and preeclampsia (AOR=7.94, 95% CI: 2.22-28.37, P=0.001) were important determinant factors for birth asphyxia. The case fatality rate of perinatal asphyxia was 37.5%. Conclusion and Recommendations. Prevalence and mortality of asphyxia were high. Prolonged labor, presence of meconium, and preeclampsia were determinant factors for birth asphyxia. Early detection and intervention of high-risk mothers should be carried out by health care providers, and mothers should be monitored with partograph during labor.